A Clinically-Reasoned Approach to Manual Therapy in Sports Physical Therapy - Steven Short; Matthew Tuttle; Dillon Youngman (North American Sports Medicine Institute, 2023)
Symptom modification techniques have been recently dichotomously labeled as either passive or active therapies. Active therapy such as exercise has been rightfully advocated for while "passive" therapies, mainly manual therapy have been regarded as low value within the physical therapy treatment spectrum. In sporting environments where physical activity and exercise are inherent to the athletic experience, the utilization of exercise-only strategies to manage pain and injury can be challenging when considering the demands and qualities of a sporting career which include chronically high internal and external workloads. Participation may be impacted by pain and its influence on related factors such as training and competition performance, career length, financial earning potential, educational opportunity, social pressures, influence of family, friends, and other key stakeholders of their athletic activity. Though highly polarizing viewpoints regarding different therapies create black and white "sides," a pragmatic gray area regarding manual therapy exists in which proper clinical reasoning can serve to improve athlete pain and injury management. This gray area includes both historic positive reported short-term outcomes and negative historical biomechanical underpinnings that have created unfounded dogma and inappropriate overutilization. Applying symptom modification strategies to safely allow the continuation of sport and exercise requires critical thinking utilizing not only the evidence-base, but also the multi-factorial nature of sports participation and pain management. Given the risks associated with pharmacological pain management, the cost of passive modalities like biophysical agents (electrical stimulation, photobiomodulation, ultrasound, etc), and the indications from the evidence-base when combined with active therapies, manual therapy can be a safe and effective treatment strategy to keep athletes active. # Level of Evidence 5